Α‐Co(OH)2 Thin‐Layered Cactus‐Like Nanostructures Wrapped Ni3S2 Nanowires: A Robust and Potential Catalyst for Electro‐oxidation of Hydrazine. Issue 5 (3rd March 2021) - Xie, Yichun; Wang, Zining; Wang, Hui; Lu, Lei; Subramanian, Palaniappan; Ji, Shan; Kannan, Palanisamy
Abstract: It is of significant urgency to fabricate highly active catalysts for electro‐oxidation of hydrazine for application in direct hydrazine fuel cells (DHFCs). Thus, in this work we grow three‐dimensional (3‐D) α‐Co(OH)2 thin‐layered cactus‐like nanostructures (shell) on the surface of Ni3 S2 nanowires (core) enveloped nickel (Ni) foam substrate. HRTEM images clearly reveal that the α‐Co(OH)2 thin‐layered cactus‐like nanostructures (shell) are evenly surrounded on the surface of Ni3 S2 nanowires (core). Notably, α‐Co(OH)2 /Ni3 S2 thin‐layered cactus‐like nanowires modified Ni foam displays an enhanced electro‐oxidation of hydrazine (340 mA current response and the onset oxidation potential of −1.10 V) than α‐Co(OH)2 sponge‐like, and Ni3 S2 nanowire structures. The obtained enhanced electro‐catalytic response is mainly due to its electron rich Ni active centers, larger electrochemically active surface area, higher electrical conductivity, and porous surface‐structure formed by growing α‐Co(OH)2 thin‐layered cactus‐like nanostructures on the Ni3 S2 nanowires, henceforth increasing the inherent activity and the number of available active sites/spots. Further, the α‐Co(OH)2 /Ni3 S2 thin‐layered cactus‐like nanowire catalyst shows notable stability (stable for more than a week) towards electro‐oxidation of hydrazine. Thus, as fabricated cactus‐like thin‐layered α‐Co(OH)2 /Ni3 S2 core‐shell nanowires catalyst can be considered as potential and robust catalyst for electro‐oxidation of hydrazine. Abstract : Wire wrap : In this work, cactus‐like thin layered nanosheets of α‐Co(OH)2 wrapped on the surface of Ni3 S2 nanowires were prepared, and effectively used toward electro‐oxidation of hydrazine in alkaline medium for the first time. As prepared α‐Co(OH)2 /Ni3 S2 thin‐layered cactus‐like nanowires modified Ni foam electrode displayed an enhanced electro‐oxidation of hydrazine (340 mA current response and lowermost onset oxidation potential; −1.10 V) than α‐Co(OH)2 sponge‐like, and Ni3 S2 nanowire structures modified Ni foams.